Pengaruh penggunaan tepung bonggol talas terfermentasi sebagai pengganti jagung terhadap konsumsi dan kecernaan protein kasar dan energi pada babi peranakan - Maria I Fale; I Made S Aryantha; Tagu Dodu (Jurnal Peternakan Lahan Kering, 2019)
The study aimed at evaluating the effect of substituting corn meal using fermented Taro curculionem substituting corm meal on Protein and energy intake and digestibility of crossbred pigs. There were 12 crossbred pigs 3-4 months of age and initial body weight 15 – 24 kg (avg 17.70 kg; CV 16.18) used in the study. Block design 4 treatments with 3 replicates procedure was used in the trial. The 4 treatment feeds offered were: feed without fermented Taro corm (R0), feed with fermented Taro substituting 5% corm (R1); feed with fermented Taro substituting 10% corm (R2); and feed with fermented Taro substituting 15% corm (R3). The results showed that effect of substituting corn with fermented Taro corm up to 15% is not significant (P>0.05) on either dry matter or organic matter intake or digestibility. The conclusion is that fermented Taro corm can be included 15% in the feed as at level 15% tend to reduce both protein and energy intake and digestibility. The suggestion is that fermented Taro corm can be used up to 15% at the similar age and state of pigs.